A coursebook on reading : Basic Reading Skills & Advanced Reading Skills - Nguyen, Thu Huong (CanTho University publishing house, 2012)
There are two main parts in this material, namely basic reading skills and advanced reading skills which are implemented through a series of various topics related to culture, health, living environment and so on.